2017
DOI: 10.1007/s00216-017-0398-3
|View full text |Cite
|
Sign up to set email alerts
|

Moving from millifluidic to truly microfluidic sub-100-μm cross-section 3D printed devices

Abstract: Three dimensional (3D) printing has generated considerable excitement in recent years regarding the extensive possibilities of this enabling technology. One area in which 3D printing has potential, not only for positive impact but also for substantial improvement, is microfluidics. To date many researchers have used 3D printers to make fluidic channels directed at point of care or lab on a chip applications. Here, we look critically at the cross-sectional sizes of these 3D printed fluidic structures, classifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 51 publications
0
92
1
Order By: Relevance
“…Second, we used a 4% PEGDA solution: we found that 3% PEGDA was not sufficient to eliminate the undesired migration of analyte while 5% PEGDA tended to block the channels and prevent fluid flow. While these COC devices are compatible with standard 2D micromachining, we note that it is also feasible to 3D print microfluidic devices from PEGDA . These 3D printed devices may be appealing for future analyses to avoid this photografting step.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we used a 4% PEGDA solution: we found that 3% PEGDA was not sufficient to eliminate the undesired migration of analyte while 5% PEGDA tended to block the channels and prevent fluid flow. While these COC devices are compatible with standard 2D micromachining, we note that it is also feasible to 3D print microfluidic devices from PEGDA . These 3D printed devices may be appealing for future analyses to avoid this photografting step.…”
Section: Resultsmentioning
confidence: 99%
“…While this approach is suitable to fabricate microchannels with different cross-sections, the resolution of printed parts is not high enough due to inherent limitations of FDM printing. Although direct fabrication of microchannels using SLA and digital light processing (DLP) method is a suitable candidate, inertial microfluidic devices often operate in channels in the order of micrometer (e.g., rectangular with 200 µm width and 40 µm height) where removing resin residuals from the channel is a challenging issue 41 .…”
mentioning
confidence: 99%
“…Although the channel walls and edges are less smooth compared to PDMS chips, this is often negligible, as flow-based microfluidics for cultivation of tissues or whole organisms often do not require high-resolution chips with mm details. Furthermore, even complex systems including valves have been achieved using this method of production (Beauchamp et al, 2017;Bhattacharjee et al, 2016;Gong et al, 2016), and it is foreseeable that such approaches will ultimately be able to compete with soft lithography. A clear advantage is the minimal equipment required (plastic printers are available starting from a few hundred US dollars) and the high level of automation (designs from other groups can simply be imported and manufactured without any additional manual work).…”
Section: Discussionmentioning
confidence: 99%